The Caci Dance as Informal Education for Developing Youth Character and Social Skills in Manggarai - Yohanes Vakundus Maka; Stofiani Susana Lima; Nirwaning Makleat; Abdul Syukur (JGK (Jurnal Guru Kita), 2026)
This study explores the role of the Caci dance in Manggarai East Nusa Tenggara as a form of informal education that develops youth character and social skills. Using a qualitative ethnographic approach data were collected through semi-structured interviews with active and former dancers, cultural leaders and participant observations of live performances supported by video analysis. The findings show that Caci functions as an informal learning system that transmits essential values such as discipline, courage, humility, perseverance, respect and emotional regulation. It also helps develop socio-emotional skills like communication, collaboration, empathy, conflict resolution and social awareness. These values are expressed through costume preparation, symbolic rituals, movement patterns, chantingand reconciliation. The study proposes a conceptual model explaining how ritual participation supports the acquisition and application of social-emotional skills in everyday life. It highlights the importance of culturally based learning practices in complementing formal education while preserving indigenous wisdom and contributes to broader discussions on informal learning and socio-emotional development.